2020
DOI: 10.1186/s12014-020-09301-x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical effects of remote ischaemic conditioning in human kidney transplants revealed by quantitative proteomics

Abstract: Background Remote ischaemic conditioning (RIC) is currently being explored as a non-invasive method to attenuate ischaemia/reperfusion injuries in organs. A randomised clinical study (CONTEXT) evaluated the effects of RIC compared to non-RIC controls in human kidney transplants. Methods RIC was induced prior to kidney reperfusion by episodes of obstruction to arterial flow in the leg opposite the transplant using a tourniquet (4 × 5 min). Although RIC did not lead to clinical improvement of transplant outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…Unfortunately, the Ig-like species described above could not be included due to lacking a mature porcine gene entry ( Supplementary Figure 2 ). Mirroring the human CONTEXT study [19], there was an accumulation of muscle-derived and extracellular matrix assembly proteins in the renal tissue following RIC, including the collagens COL1A2, COL2A1, COL4A2, COL4A, COL6A3, fibrillin and fibulin ( Figure 2, Supplementary Figure 2 ), although no tourniquet on a limb but rather clamping of the aorta was used in the present porcine study. Additionally, upregulation of factors associated with innate immunity such as lysosome-associated membrane glycoprotein 1 (LAMP1), neutrophil cytosol factor 2 (NCF2), leucine-rich alpha-2-glycoprotein (LRG1), myeloperoxidase (MPO), and properdin (CFP) were observed, suggesting the technique provoked the activation of tissue remodeling cascades within the organ itself.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Unfortunately, the Ig-like species described above could not be included due to lacking a mature porcine gene entry ( Supplementary Figure 2 ). Mirroring the human CONTEXT study [19], there was an accumulation of muscle-derived and extracellular matrix assembly proteins in the renal tissue following RIC, including the collagens COL1A2, COL2A1, COL4A2, COL4A, COL6A3, fibrillin and fibulin ( Figure 2, Supplementary Figure 2 ), although no tourniquet on a limb but rather clamping of the aorta was used in the present porcine study. Additionally, upregulation of factors associated with innate immunity such as lysosome-associated membrane glycoprotein 1 (LAMP1), neutrophil cytosol factor 2 (NCF2), leucine-rich alpha-2-glycoprotein (LRG1), myeloperoxidase (MPO), and properdin (CFP) were observed, suggesting the technique provoked the activation of tissue remodeling cascades within the organ itself.…”
Section: Resultsmentioning
confidence: 96%
“…Our previous work in a porcine model of kidney transplantation suggested a beneficial effect of RIC on early graft perfusion and function evidenced by a significantly improved renal plasma perfusion and glomerular filtration rate (GFR) [18]. However, when RIC was applied to kidney transplant patients in a clinical trial (CONTEXT), no clinical benefit was observed, although the trial did reveal distinct subclinical effects on kidney transplants at the molecular level [17, 19, 20]. We have therefore revisited our RIC study carried out in pigs that had shown potential positive effects of RIC which stimulated us to design the clinical CONTEXT study.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the Ig-like species described above could not be included due to lacking a mature porcine gene entry (Additional file 1: Figure S2). Mirroring the human CONTEXT study [19], there was an accumulation of muscle-derived and extracellular matrix assembly proteins in the renal tissue following RIC, including the collagens COL1A2, COL2A1, COL4A2, COL4A, COL6A3, fibrillin and fibulin (Fig. 2, Additional file 1: Figure S2), although no tourniquet on a limb but rather clamping of the aorta was used in the present porcine study.…”
Section: Resultsmentioning
confidence: 96%
“…Our previous work in a porcine model of kidney transplantation suggested a beneficial effect of RIC on early graft perfusion and function evidenced by a significantly improved renal plasma perfusion and glomerular filtration rate (GFR) [18]. However, when RIC was applied to kidney transplant patients in a clinical trial (CONTEXT), no clinical benefit was observed, although the trial did reveal distinct subclinical effects on kidney transplants at the molecular level [17,19,20]. We therefore revisited our RIC study carried out in pigs which showed potential positive effects of RIC, and which had stimulated us to design the clinical CONTEXT study.…”
Section: Open Accessmentioning
confidence: 99%
“…Nikkola et al enrolled 13 patients who had ruptured intracranial aneurysms and analyzed their DNA methylation and transcriptome profiles before and after a one-time RIC intervention [11]. Thorne et al collected six pairs of human kidney transplant patients and observed the transient upregulation of several acute phase response proteins (SAA1, SAA2, and CRP) in the plasma at both one and five days post-RIC treatment [12].…”
Section: Introductionmentioning
confidence: 99%